Implementation of the Gamification Learning Method in Increasing Student Learning Motivation in the Subject of Al-Qur'an Hadith - Durrotul Hitami; Taufiqur Rahman; Erwan Widiantoro; Freti Sinta; Khoirul Ikhsan (Global Action and Education for Society, 2025)
The use of gamification learning methods in Madrasah Aliyah can enhance student motivation and engagement in the learning process, allowing them to be more active and enthusiastic in achieving their academic goals. By applying gamification elements, teachers can create a more interactive and enjoyable learning environment, thereby motivating students to learn and achieve better academic performance. There are two issues that are the focus of the research, first, how is the implementation of the gamification method in increasing student learning motivation in the subject of Al-Qur'an Hadith at Madrasah Aliyah Al-Falah Payuddan Karangsokon Guluk-Guluk Sumenep? Second, what are the supporting and inhibiting factors in the implementation of the gamification method in increasing student motivation in the subject of Al-Qur'an Hadith at Madrasah Aliyah Al-Falah Payuddan Karangsokon Guluk-Guluk Sumenep? The research approach used in this study is a qualitative approach, where the research results obtained are in the form of descriptive data. The data collection techniques used by the researcher are thru observation, interviews, and documentation. The data sources in this study are the school principal, the Qur'an and Hadith subject teachers, and the students. The data analysis was conducted by reducing the data, presenting the data, and verifying the obtained data. The research findings indicate that, first, it is effective because after implementing the gamification method during lessons, more and more students gradually understand the Quran and Hadith. Secondly, the supporting factor for the implementation of gamification is the attention of parents toward their children's education, while the hindering factors are the lack of school facilities that support the application of gamification and the lack of parental attention toward their children's education. The implication of this research is that this gamification method can serve as a reference for adjusting teaching methods in the education sector, in addition to being a reference for Islamic education teachers across all levels and stages of education.